1976
DOI: 10.2307/145430
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Incomes of Men and Women Physicians: An Exploratory Analysis

Abstract: Income differences between men and women physicians are analyzed using data from the Americal Medical Association's 1973 Eighth Periodic Survey of Physicians. While women tend to possess less favorable professional characteristics in terms of income-earning potential, the returns to many characteristics associated with higher incomes are greater for women than for men. Additional evidence on differences in weekly hours worked is presented in an effort to explain the lower incomes of women doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 11 publications
6
29
0
Order By: Relevance
“…Further, the positive coefficient for the interaction term between days not worked and the dummy variable of services by appointment suggests that physicians working outside the official opening hours earn a higher income, all else equal. 8 In accordance with earlier studies, age (age squared) enters significantly positive (negative) -at least in the male regression -indicating a positive but diminishing impact of a physician's work experience on annual earnings (see, e.g., Kehrer, 1976;Langwell, 1982;Ohsfeldt and Culler, 1986;Bashaw and Heywood, 2001). Residential length exhibits a positive impact on earnings, which is also in line with previous research (see Ohsfeldt and Culler, 1986).…”
Section: Specification and Estimationsupporting
confidence: 87%
See 2 more Smart Citations
“…Further, the positive coefficient for the interaction term between days not worked and the dummy variable of services by appointment suggests that physicians working outside the official opening hours earn a higher income, all else equal. 8 In accordance with earlier studies, age (age squared) enters significantly positive (negative) -at least in the male regression -indicating a positive but diminishing impact of a physician's work experience on annual earnings (see, e.g., Kehrer, 1976;Langwell, 1982;Ohsfeldt and Culler, 1986;Bashaw and Heywood, 2001). Residential length exhibits a positive impact on earnings, which is also in line with previous research (see Ohsfeldt and Culler, 1986).…”
Section: Specification and Estimationsupporting
confidence: 87%
“…Both variables account for the productivity of physicians (see Kehrer, 1976;Langwell, 1982). Further, our sample contains information on the demand for physician services of three age groups: young patients (below 30 years), patients between 31 and 60 years, and elderly (above 60 years).…”
Section: > Tablementioning
confidence: 99%
See 1 more Smart Citation
“…An obvious example is the [8]. Some people hypothesize that this sex salary gap can be explained by the constraints of family responsibilities leading to decreased hours and productivity [9,10]. That may have been the case in the past, but recent studies found that this gender salary gap cannot be explained by age, experience, specialty, practice type, work hours, research productivity, or clinical revenue [8,11].…”
Section: Female Physiciansmentioning
confidence: 99%
“…Female physicians earn less money than male physicians on average (Income, 2003), a fact that remains even when statistically controlling for factors such as area of specialization, age, number of patients seen and years in practice (Kehrer, 1976;Langwell, 1982;Median Unadjusted Income, 2000;Ohsfeldt & Culler, 1986 another independent variable, the current study attempts to better understand how gender, as a process, is accomplished in the medical encounter.…”
Section: Doing Gender In the Medical Encountermentioning
confidence: 99%